2008 2nd International Conference on Bioinformatics and Biomedical Engineering 2008
DOI: 10.1109/icbbe.2008.698
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman Spectroscopy Monitor Methemoglobin Induced by Sodium Nitrite in Whole Blood

Abstract: In this paper, we demonstrated that micro-Raman spectroscopy could be used to detect methemoglobin in whole blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The main intensity differences locate at around 677 cm −1 ( ν 7 ), 1,375 cm −1 ( ν 4 ), 1,586 cm −1 ( ν 37 ), 1,638 cm −1 ( ν 10 ). These results are in agreement with the other reports (Shen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The main intensity differences locate at around 677 cm −1 ( ν 7 ), 1,375 cm −1 ( ν 4 ), 1,586 cm −1 ( ν 37 ), 1,638 cm −1 ( ν 10 ). These results are in agreement with the other reports (Shen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Shen et al . () monitored MetHb induced by sodium nitrite with 514 nm excitation, they observed that the intensity of low‐spin marker band at 1,585 cm −1 and the oxygenic indicator band at 1,637 cm −1 decreased in MetHb. These studies showed the tremendously potential of Raman spectroscopy as a new approach for detection of MetHb.…”
Section: Introductionmentioning
confidence: 99%